2008
DOI: 10.3748/wjg.14.6632
|View full text |Cite
|
Sign up to set email alerts
|

Azoxymethane-induced rat aberrant crypt foci: Relevance in studying chemoprevention of colon cancer

Abstract: The pathogenesis of colon cancer involves sequential and multistep progression of epithelial cells initiated to a cancerous state with defined precancerous intermediaries. Aberrant crypt foci (ACF) represent the earliest identifiable intermediate precancerous lesions during colon carcinogenesis in both laboratory animals and humans. ACF are easily induced by colon-specific carcinogens in rodents and can be used to learn more about the process of colon carcinogenesis. For over two decades, since its first disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 18 publications
2
83
0
Order By: Relevance
“…42,43 Previous reports indicated that, rather than simply being oncogenic, high chromosome instability from defects in mitotic machinery can be both oncogenic and tumor suppressive in an environment-dependent manner. 20,22,36 In our AOM-induced tumorigenesis assay, the SGO1 +/-mice showed a significant increase in size and frequency of ACF, which are precursor lesions of colonic tumors, [31][32][33][34][35] and an increased number of colonic tumors at the endpoint, indicating that the SGO1 defect can be an enhancing factor for colonic tumorigenesis. This observation is reminiscent of our previous results on colonic tumorigenesis with BubR1 haploinsufficiency mice, which show a spindle checkpoint defect and high mitotic chromosome instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Previous reports indicated that, rather than simply being oncogenic, high chromosome instability from defects in mitotic machinery can be both oncogenic and tumor suppressive in an environment-dependent manner. 20,22,36 In our AOM-induced tumorigenesis assay, the SGO1 +/-mice showed a significant increase in size and frequency of ACF, which are precursor lesions of colonic tumors, [31][32][33][34][35] and an increased number of colonic tumors at the endpoint, indicating that the SGO1 defect can be an enhancing factor for colonic tumorigenesis. This observation is reminiscent of our previous results on colonic tumorigenesis with BubR1 haploinsufficiency mice, which show a spindle checkpoint defect and high mitotic chromosome instability.…”
Section: Discussionmentioning
confidence: 99%
“…4A). [31][32][33][34][35] Defects in chromosome cohesion are implicated in chromosome instability and colonic the mRNA expression, SGO1 protein level was also lower in SGO1 +/-cells than that in WT cells ( Fig. 1E and F).…”
Section: Sgo1mentioning
confidence: 99%
“…In this protocol rats were treated with PRE mixed diet for 1 week before induction of ACF by DMH in order to study the modulating effect of xenobiotic metabolism in rat liver and the final outcome marker, ACF at 5 weeks of the experiment (Raju, 2008). Purple rice extract reduced the total number of ACF when compared to DMH-treated rats but the effects of the dosage were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Not only can these lesions modify barrier function, but high-dose chemotherapy regimens can also modify the digestive and absorptive function of the GI tract (Rubenstein et al, 2004). Several in vivo rodent models can be induced to develop premalignant lesions and tumors of the buccal cavity, esophagus, stomach, small intestine and colon that are similar to those observed in humans and are amenable to study interactions with dietary components (Chen & Lin, 2010;Garman et al, 2012;Lai et al, 2010;Raju, 2008;Raju & Bird, 2003;Tanaka, 2012;Zeineldin & Neufeld, 2013;Zhang & Moss, 2012). Such models could be useful for assessing not only the influence of cancer on NM uptake from the gut, but also beneficial targeting of ingested pharmaceutical or imaging NMs to gastrointestinal tumors.…”
Section: Models Of Epithelial Malignanciesmentioning
confidence: 99%